2010
DOI: 10.3113/fai.2010.0398
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Excision of Posterior Ankle Bony Impingement for Early Return to the Field: Short-term Results

Abstract: Arthroscopic treatment for posterior ankle bony impingement syndrome was minimally invasive and suitable for athletes who desire an early return to sports activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 10 publications
0
40
0
3
Order By: Relevance
“…20,[44][45][46][47] More than 95% of athletes return to the same level of sport. 19,45,48,49 Open procedures have shown similar return to sport outcomes, but with longer recovery times. [50][51][52] Patients obtain pain-free range of motion and small increases in dorsiflexion postoperatively.…”
Section: Clinical Outcomesmentioning
confidence: 83%
See 1 more Smart Citation
“…20,[44][45][46][47] More than 95% of athletes return to the same level of sport. 19,45,48,49 Open procedures have shown similar return to sport outcomes, but with longer recovery times. [50][51][52] Patients obtain pain-free range of motion and small increases in dorsiflexion postoperatively.…”
Section: Clinical Outcomesmentioning
confidence: 83%
“…34,43,49,53 Most of the literature on athletes involves elite soccer players and dancers. Arthroscopically treated, athletes return sport faster than those who undergo open procedures.…”
Section: Clinical Outcomesmentioning
confidence: 99%
“…Average time to return to sports or activities was 5.9 weeks to 5.8 months. 23,[60][61][62][63]65,66,[70][71][72] Open excision of the os trigonum through PM or PL approaches were effective and safe in the patients with os trigonum syndrome. 29,73 Previous studies reported significant improvement of AOFAS scores, and average AOFAS scores were 87.6 to 100.0 points at the final postoperative visit.…”
Section: Clinical Outcomes Os Trigonummentioning
confidence: 98%
“…23 Arthroscopic os trigonum excision can be performed from either a lateral or a posterior approach. 23,[60][61][62][63][64][65][66][67] The authors prefer prone over lateral decubitus position because it provides a more direct approach to the os trigonum, decreases the risk of instrument skiving off toward the neurovascular bundles, and simultaneously allows performance of the procedure for FHL pathology.…”
Section: Arthroscopic Approachmentioning
confidence: 98%
“…25 Conversely, patients undergoing ankle arthroscopic excision do not wear a cast after surgery and they are advised to limit the range of motion and to protected the load in the first twenty-four hours postoperatively. 26 On the other hand, in surgical procedures of the ankle more invasive than SA, patients are encouraged to exert weight after surgery. In patients undergoing SA, if a physiotherapist is involved in stage 1, in order to prevent/manage any complications, he/she must be present as a counselor and must refer every unusual condition (after clinical evaluation) which may compromise the postoperative course.…”
Section: Stage 1 (Immobilization and Pain)mentioning
confidence: 99%